Bonamia -free flat oyster ( Ostrea edulis L.) seed for restoration projects: non-destructive screening of broodstock, hatchery production and test for Bonamia -tolerance - Kamermans, Pauline; Blanco, Ainhoa; van Dalen, Pim; Engelsma, Marc; Bakker, Nienke; Jacobs, Pascalle; Dubbeldam, Marco; Sambade, Inés M.; Vera, Manuel; Martinez, Paulino (Aquatic living resources (Montrouge), 2023)
Native (flat) oyster ( Ostrea edulis ) beds, once a major component of the North Sea, largely disappeared from the region in the late 19th century. Flat oyster restoration is taking place at a number of locations in the North Sea. When flat oyster beds are restored in areas where O. edulis is functionally extinct it is advised to treat these as disease-free areas. Adult oysters were collected in the Dutch Delta area which is infected with the pathogenic parasite Bonamia ostreae . The aim of this research was to obtain Bonamia -free seed from parents collected in a Bonamia -infected area. In addition, the oysters were analysed to identify candidate genomic regions related to bonamiosis tolerance and exposed to Bonamia in the field to assess survival compared to a naïve control group. With the aid of a non-destructive screening method, Bonamia -free broodstock were selected. These oysters produced Bonamia -free larvae and seed. For comparison, broodstock oysters were collected in the Dutch Wadden Sea, an area free of Bonamia . These oysters also produced Bonamia -free larvae and seed. To study if the Delta area oysters had developed a degree of resistance to the disease, while the naïve Wadden Sea oysters had not, seed of both groups was challenged in Lake Grevelingen where Bonamia occurs. Survival of the pre-selected Bonamia -free oysters was significantly higher than the naïve group. Samples of seed were analysed for association of candidate genetic markers related to bonamiosis tolerance. A higher percentage of individuals with tolerance-associated marker genotypes was found in the screened group compared to the naïve one. However, mortality of the naïve group could not be related to Bonamia presence. Further challenge tests are needed before firm conclusions regarding the genetic markers can be made. The results show that hatchery production of Bonamia -free and potentially Bonamia -tolerant flat oysters is possible.